Analisis Yuridis Atas Perjanjian Kerjasama Penyediaan Air Besih Di Kota Medan Antara PDAM Tirtanadi Dengan PT. Tirta Lyonnaise Medan Tahun 2000 - Indra Kurniawan Nasution; Tan Kamello; Suhaidi Suhaidi; Jelly Leviza (Universitas Sumatera Utara, 2019)
Abstract.This research uses normative research type with the consideration that the starting point of the research is the analysis of the law of agreement, the nature of research in use is analytical descriptive that is by collecting data through document studies by using qualitative data analysis with emphasis on the form and obstacles of agreement and dispute settlement agreement.Based on the results of the research is known that basically Agreement of Cooperation of Water Supply Besih in Medan City Between PDAM Tirtanadi With PT. TirtaLyonnaise Medan was born from the principle of freedom of contract already meet the provisions in Article 1320 Civil Code and Law No.25 of 2007 on investment, in implementing the cooperation agreement there are several obstacles that occur there are juridical such as taxation, labor, non juridical such as illegal levies, the manner of dispute resolution in this cooperation agreement is set out in article 18 with out court through arbitrators and experts Keywords: cooperation agreement, water supply, dispute settlemen